Survey Inter-Reference Recency Based Page Replacement Policies to Cope with Weak Locality Workloads - Saud, Arjun Singh (Kathford Journal of Engineering and Management, 2018)
Least recently used (LRU) makes bold assumption on recency factor only which made LRU miss behave with weak locality workloads. If the “frequency”, of each page reference is taken into consideration, it will perform better in the case where workload has weak locality. Frequency count leads to serious problem after a long duration of reference stream because it cannot cope with change in locality. Reuse distance or inter reference recency (IRR) of a block is equal to number of distinct pages accessed between recent consecutive or correlated access of that particular block. Many recent variations of LRU use IRR rather than recency such that LRU can be made friendly with weak locality workloads. This papers surveys LRU variants that use IRR to make page replacement decision.